Perancangan Aplikasi Booking Paket Umroh Berbasis Website Menggunakan Metode Agile (Studi Kasus: PT Zuwar Haramaen Zahra Fahira) - Ahmad Aldi Mumtaz; Muhammad Daffa Insani; Rafie Fathurrachman; Saprudin (CV. Multi Kreasi Media, 2025)
This research aims to design and develop a web-based umrah booking application to facilitate online reservations for prospective pilgrims and support efficient, integrated booking management for administrators. The Agile method is used as the system development approach, characterized by iterative cycles and flexibility to adapt to User needs. The application is built using HTML, CSS, JavaScript, PHP, and MySQL. The case study is conducted at PT Zuwar Haramaen Zahra Fahira, which previously used manual booking processes. The developed system includes features such as account registration, package selection, payment confirmation, and dashboards for both Users and admins. The results show that the application improves booking efficiency, record accuracy, and accessibility of information for both customers and management.